2008
DOI: 10.1007/s12098-008-0209-0
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Diseases and Corticosteroids

Abstract: Steroids (corticosteroids) are anti-inflammatory drugs. Corticosteroids are used in many pulmonary conditions. Corticosteroids have a proven beneficial role in asthma, croup (Laryngotracheobronchitis), decreasing the risk and severity of respiratory distress syndrome (RDS), allergic bronchopulmonary aspergillosis, interstitial lung disease, hemangioma of trachea, Pulmonary eosinophillic disorders. Role of corticosteroids is controversial in many conditions e.g. idiopathic pulmonary hemosiderosis, bronchiolitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…The largest series of patients in literature showing response in IPH with GFD has been reported by Khemiri et al and Sethi et al [7,13]. Khemiri et al reported clinical and radiological improvement in both pulmonary and gastrointestinal symptoms with corticosteroid treatment combined with a gluten-free diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest series of patients in literature showing response in IPH with GFD has been reported by Khemiri et al and Sethi et al [7,13]. Khemiri et al reported clinical and radiological improvement in both pulmonary and gastrointestinal symptoms with corticosteroid treatment combined with a gluten-free diet.…”
Section: Discussionmentioning
confidence: 99%
“…Pacheco et al reported that GFD induced remission in IPH can be on long-term basis up to 4 years [16]. Sethi et al reported a patient who was initially followed up as IPH [7]. The pulmonary symptoms persisted despite steroids and azathioprine over a follow up period of two and half year.…”
Section: Discussionmentioning
confidence: 99%
“…4 Current therapies include anti-inflammatory drugs and bronchodilators, but unfortunately these therapies are often associated with many side-effects. 5 Thus, a possible role for alternative therapies aimed at controlling the asthmatic condition and improving quality of life has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, immunosuppressant drugs, such as corticosteroids, among them methylprednisolone (MP), play an integral role in anti-inflammatory treatments of pulmonary diseases, particularly in asthma, acute lung injury, and acute respiratory distress syndrome (Silva et al, 2009;Barnes, 2011;Marik et al, 2011;Liu et al, 2013). The efficacy of corticosteroids in suppressing lung inflammation has been confirmed by both systemic administration and inhalation (Sethi and Singhal, 2008;Higham et al, 2015). MP has been shown to attenuate acute lung injury, induced with bacterial endotoxin lipopolysaccharide (LPS), via promoting macrophage polarization into the M2 subset (Tu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%